Development of a Parental Feeding Goal Measure: The Family Mealtime Goals Questionnaire - Snuggs, Sarah; Houston-Price, Carmel; Harvey, Kate (Frontiers in Psychology, 2019)
It is well established that parents’ feeding practices predict children’s eating behaviors. However, there has been little research into parents’ mealtime goals – their desired outcomes for family mealtimes. These goals, and potential conflicts between them, may be important both in explaining parents’ feeding practices and improving children’s eating behaviors, as health behavior change is more likely to be achieved by programmes and interventions that are aligned with an individual’s goals. The objectives of this study were to develop a reliable and valid measure that captures parental mealtime goals, and to describe parents’ endorsement of these goals. Online questionnaire methods were used to design and test the Family Mealtime Goal Questionnaire with 1,140 parents and carers of at least one child aged from 1 to 16 years. Exploratory qualitative analysis, Principal Components Analysis, Confirmatory Factor Analysis and test-retest analysis (using intraclass correlations) were conducted to establish the psychometric properties of the instrument. An 18-item questionnaire was produced with seven dimensions: stress/conflict avoidance, homemade food, shared family food, family involvement in mealtimes, price, occasional treats, and high/low fat regulation. Some differences were found in the goal structure of parents of children of different ages but stress/conflict avoidance was the most strongly endorsed mealtime goal for all age groups. The Family Mealtime Goals Questionnaire provides a useful measure of parents’ feeding motivations. It will facilitate large-scale research into the relationships between parents' feeding goals and practices and could inform the design of more effective healthy eating interventions that target specific feeding goals.